Implementasi Kebijakan Penanggulangan Kemiskinan dalam RPJMD Berdasarkan Perspektif Grindle (Studi di Kabupaten Lamongan) - As'adi, David; Rozikin, Mochammad; Khabibi, A. Rizal (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2024)
Poverty remains a classic issue in Indonesia's development agenda. High poverty rates persist in various regions, including in Lamongan Regency, prompting the government to formulate public policies to address this challenge. This study aims to investigate the implementation of poverty alleviation policy in Lamongan Regency as outlined in the Regional Medium-Term Development Plan (RPJMD) for the period 2021-2026 and the influencing factors. The study employs Grindle's (1980) framework as a lens to explore the factors affecting policy implementation. Using a qualitative method with a descriptive approach, the study collected primary and secondary data through interviews, document analysis, and literature review. The results indicate that the poverty alleviation policy in Lamongan Regency has demonstrated commendable performance, evidenced by a consecutive reduction in the poverty rate by 12.53% in 2022 and 12.42% in 2023. This performance is influenced by factors related to policy content and the implementation context. The study provides recommendations for policymakers to consider aspects related to policy content (clear goal-setting, targets, and implementation mechanisms) and the implementation context (collaborative governance strategy, political considerations, and flexibility), particularly in addressing poverty in a region.